Performance of West African Firms in Mergers and Acquisitions : Array - Okofo-Dartey, Emmanuel; Kwenda, Farai (Acta Universitatis Danubius. Œconomica, 2022)
Mergers and acquisitions (M&As) have become essential pathways firms use to access new markets and capabilities. As a result, firms located in West Africa are also taking advantage of M&As to reposition themselves to expand in size and become more profitable. However, the extent to which these firms have been improving their performances regarding increased profits and growth in their sizes following their M&A executions remains an issue that has not been investigated. Using a firm-level dataset of 23 quoted firms from West Africa gleaned from the Bloomberg Database from 2000 to 2017, the present study, therefore, employs the difference generalised method of moments (GMM) technique to investigate whether M&A deals by firms from West Africa are value-adding or destroying, particularly in the areas of profitability and growth in sizes. The study results indicate that West African firms that undertake M&As experience growth in profits in the immediate four years after acquisition deals compared to the two years preceding these transactions. However, no evidence is obtained for growth in the sizes of these firms in the initial four years after M&A transactions. Following these findings, managers of West African firms desirous of growth in profits could rely on M&As as one possible route to realize this objective, even though they may not be able to use M&As to improve on their sizes in the short-term period after deals are completed.